Detection and Characterization of Clinical Bordetella trematum Isolates from Chronic Wounds - Christian Buechler; Claudio Neidhöfer; Thorsten Hornung; Marcel Neuenhoff; Marijo Parčina (Pathogens, 2021)
Bordetella trematum is a relatively newly discovered and potentially frequently overlooked Bordetella species, mostly isolated from chronic wounds and predominantly in those of the lower extremities. Its susceptibility profile and clinical significance is still debated, given the limited amount of available data. We contribute providing a molecular and phenotypical analysis of three unique clinical B. trematum isolates detected between August 2019 and January 2020 to aid the matter. Cryo-conserved isolates were subcultured and re-identified using various routine means of identification. Bacterial genomes were fully Illumina-sequenced and phenotypical susceptibility was determined by broth microdilution and gradient-strip tests. All isolates displayed increased susceptibility to piperacillin–tazobactam (<2/4 mg/L), imipenem (<1 mg/L), and meropenem (<0.047 mg/L), whereas they displayed decreased susceptibility to all tested cephalosporins and fluoroquinolones (according to PK-PD, EUCAST 10.0 2020). One isolate carried a beta-lactamase (EC 3.5.2.6) and a sulfonamide resistance gene (sul2) and cells displayed resistance to ampicillin, ampicillin/sulbactam, and trimethoprim/sulfamethoxazole. All isolates carried genes conferring decreased susceptibility to aminoglycosides (aadA), fosfomycin (fosA) and fluoroquinolones (gyrB EC 5.99.1.3). Awareness that B. trematum can be resistant to trimethoprim/sulfamethoxazole is warranted.